Analisis Pemberdayaan Masyarakat Berbasis Kewirausahaan Anyaman Bambu Melalui Home Industry (Studi Tentang Pemberdayaan di Kelurahan Roworena, Kecamatan Ende Utara, Kabupaten Ende) - Ndjandji, Andrianto Umbu (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
Community empowerment must be promoted to improve the family economy. Each artisan of Roworena village independently produces handicrafts for ges content and leather, curtains, chicken cages and consumer demand in the form of chairs, tables, curtains, pots, hangers, entrepreneurial skills and knowledge. Handicrafts are made in the home industry, where all skills come from households. The purpose of the authors of this study is to see the phenomenon of community empowerment based on entrepreneurship as a strategic position in community development, because entrepreneurship is essentially independence and skills necessary for life. The research method is descriptive qualitative, which analyzes the phenomena occurring in the reproduction in the community up to the market results. In the analysis, the researcher elaborates the approach of empowerment through the aspects of enabling, empowering and protecting, so in response to the empowerment experienced by the community, the researcher in this study suggests that entrepreneurs of craft industry innovate more handicraft products and sales are more modern.